Glucocerebrosidase Mutations Cause Mitochondrial and Lysosomal Dysfunction in Parkinson’s Disease: Pathogenesis and Therapeutic Implications - Zheng, Wei; Fan, Dongsheng (Frontiers in Aging Neuroscience, 2022)
Parkinson’s disease (PD) is the second most common neurodegenerative disease and is characterized by multiple motor and nonmotor symptoms. Mutations in the glucocerebrosidase (GBA) gene, encoding the lysosomal enzyme glucocerebrosidase (GCase), which hydrolyses glucosylceramide (GlcCer) to glucose and ceramide, are the most important and common genetic PD risk factors discovered to date. Homozygous GBA mutations result in the most common lysosomal storage disorder, Gaucher disease (GD), which is classified by involvement of neurological symptoms (neuronopathic types, type 2 and 3 GD) or not (nonneuronopathic type, type 1 GD). The clinical manifestations of PD in patients with GBA mutations are indistinguishable from those of sporadic PD at the individual level. However, overarching data have indicated that GBA-associated PD patients exhibit a younger age of onset and a greater risk for cognitive impairment and psychiatric symptoms. The mechanisms underlying the increased risk of developing PD in GBA mutant carriers are currently unclear. Contributions to GBA-PD pathogenesis may include mitochondrial dysfunction, autophagy-lysosomal dysfunction, altered lipid homoeostasis and enhanced α-synuclein aggregation. Therapeutics targeting mutant GCase in PD and GD, mainly include enzyme replacement, substrate reduction, gene and pharmacological small-molecule chaperones. Emerging clinical, genetic and pathogenic studies on GBA mutations and PD are making significant contributions to our understanding of PD pathogenetic pathways, and further understanding of the interactions between GCase activity and neurodegeneration may improve therapeutic applications that slow PD progression.